Statistical language and speech processing : 5th International Conference, SLSP 2017, Le Mans, France, October 23?25, 2017, Proceedings /: 5th International Conference, SLSP 2017, Le Mans, France, October 23?25, 2017, Proceedings. (2017) - Unknown
No abstract available